Aspectos morfológicos e ultraestruturais de três ciliados de musgos da localidade de Corrêas, Petrópolis, Rio de Janeiro - Santos, Isabella Canha dos (1991)
Specimens of some of the most representative and abundant ciliates were selected from the water mass obtained through the collection and hydration in laboratory of two mosses, Sematophyllum subsimplex and Barbula sp. , found in Corrêas (Petrópolis, Rio de Janeiro, Brazil). Observations of life organisms, as well as of preparations for light rnicroscopy (Bodian's Protargol and Feulgen's Nuclear Reaction), standard scanning and transmission electron microscopy were employed. Morphological characteristics and some ultrastructural aspects have been analised, described and compared with those already presented in the literature. In this way, the results obtained brought us the recognition of three ciliate species: Epispathidium amphoriforme (Greeff, 1888); Urostyla grandis Ehrenberg, 1838 and Steinia quadrinucleata Dragesco & Njiné, 1971.